2023
DOI: 10.1007/s11096-023-01607-8
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of chronic pain management of older adults in remote and rural settings

Abstract: Background The World Health Organization predicts that the number of older adults will nearly double between 2015 and 2050. Older adults are at a higher risk of developing medical conditions such as chronic pain. However, there is little information about chronic pain and its management in older adults especially those residing in remote and rural areas. Aim To explore views, experiences, and behavioural determinants of older adults regarding chronic pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, social support was the important protective factor negatively related to physical pain in our network for both countries. Many studies have shown that people with chronic pain who report high levels of social support experience less distress and less severe pain, with higher levels of support associated with better adjustment in daily life despite the pain-related challenges [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, social support was the important protective factor negatively related to physical pain in our network for both countries. Many studies have shown that people with chronic pain who report high levels of social support experience less distress and less severe pain, with higher levels of support associated with better adjustment in daily life despite the pain-related challenges [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 From a clinical perspective, patients experiencing chronic pain are best served with multidisciplinary expertise, including those specializing in psychology, neurology, internal medicine, rheumatology, physical therapy, and others. 3 Access to multidisciplinary care is limited, and disparities exist in the management of chronic pain based on patient geographic location, 4 race/ethnicity, 5 and cultural aspects of pain. 6 Within our current structures, healthcare providers report that the needs of patients with chronic pain can be highly burdensome due to the multifactorial medical, social, and mental health aspects that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%